2012
DOI: 10.1007/s00467-012-2332-4
|View full text |Cite
|
Sign up to set email alerts
|

Late recovery of renal function by rituximab in a patient with Wegener’s granulomatosis

Abstract: This case documents a potent beneficial effect of rituximab on renal manifestation of GPA even in long-established ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Following the first report of the successful treatment of AAV with RTX, different rare clinical manifestations were reported as having been successfully treated with RTX. Some of the most important rare clinical presentations in GPA patients, which resolved following RTX, include retrobulbar granuloma [ 78 ], refractory ophthalmic [ 126 ], pachymeningitis [ 146 ], the presence of orbital inflammation [ 122 ], long-established end-stage renal disease [ 147 ], post-kidney-transplantation glomerulonephritis-related AAV [ 148 ], pituitary GPA [ 149 ], renal mass [ 150 ], gastric ulcer [ 151 ], pancreatitis [ 152 ], ophthalmoplegia [ 153 ], pyoderma gangrenosum [ 154 , 155 , 156 ], prostatitis [ 157 ] aortic inflammation [ 158 ], intestinal involvement [ 159 ], mastitis [ 160 ], aortitis [ 161 ], gingivitis [ 162 ], Isolated Pauci-Immune Pulmonary Capillaritis [ 163 ], isolated orbital GPA [ 164 ], cranial neuropathy [ 165 ], severe necrotizing scleritis [ 166 ], genital necrosis and inflammation [ 167 ], GPA-associated subcutaneous cheek odule [ 168 ], pseudo-tumoral digital nodules [ 169 ], hypertrophic pachymeningitis [ 170 , 171 ], acute myocarditis [ 172 ], palpable purpura [ 173 ], central nervous system vasculitis [ 174 ], intra-cranial hypertension [ 175 , 176 ], tracheobronchial stenosis [ 142 ], acute aortic valve regurgitation [ 177 ], GPA-mimicking meningeal tuberculosis [ 178 ], gynecological involvement [ 179 ], GPA-mimicking lung mal...…”
Section: Resultsmentioning
confidence: 99%
“…Following the first report of the successful treatment of AAV with RTX, different rare clinical manifestations were reported as having been successfully treated with RTX. Some of the most important rare clinical presentations in GPA patients, which resolved following RTX, include retrobulbar granuloma [ 78 ], refractory ophthalmic [ 126 ], pachymeningitis [ 146 ], the presence of orbital inflammation [ 122 ], long-established end-stage renal disease [ 147 ], post-kidney-transplantation glomerulonephritis-related AAV [ 148 ], pituitary GPA [ 149 ], renal mass [ 150 ], gastric ulcer [ 151 ], pancreatitis [ 152 ], ophthalmoplegia [ 153 ], pyoderma gangrenosum [ 154 , 155 , 156 ], prostatitis [ 157 ] aortic inflammation [ 158 ], intestinal involvement [ 159 ], mastitis [ 160 ], aortitis [ 161 ], gingivitis [ 162 ], Isolated Pauci-Immune Pulmonary Capillaritis [ 163 ], isolated orbital GPA [ 164 ], cranial neuropathy [ 165 ], severe necrotizing scleritis [ 166 ], genital necrosis and inflammation [ 167 ], GPA-associated subcutaneous cheek odule [ 168 ], pseudo-tumoral digital nodules [ 169 ], hypertrophic pachymeningitis [ 170 , 171 ], acute myocarditis [ 172 ], palpable purpura [ 173 ], central nervous system vasculitis [ 174 ], intra-cranial hypertension [ 175 , 176 ], tracheobronchial stenosis [ 142 ], acute aortic valve regurgitation [ 177 ], GPA-mimicking meningeal tuberculosis [ 178 ], gynecological involvement [ 179 ], GPA-mimicking lung mal...…”
Section: Resultsmentioning
confidence: 99%
“…While vascular diseases play a major role in the large series and in registry data, case reports, which are more prone to publication biases, mainly regard the more “charming” glomerular diseases and are mainly targeted at describing exceptional cases, highlighting the possibility of long-term recovery after various treatments, whether started in the pre-dialysis phase or performed during dialysis (2937, 3940) (Tab. II).…”
Section: Discussionmentioning
confidence: 99%
“…Table II summarizes the 13 case reports retrieved by our search strategy; they deal with one to two cases, and are reported from different sources (8 from Europe, 2 from Japan, 1 from Canada, and 2 from USA). The distribution of the case reports differs from that of the case series and registry data, highlighting the possibility of renal function recovery in immunologic or hematologic diseases, encompassing all the major glomerulopathies, from the rare ones, like Wegener's disease and atypical HUS, to the common ones, like IgA nephropathy or FSGS (29)(30)(31)(32)(33)(34)(35)39). However, in keeping with the important role of vascular diseases in this context, two cases (cholesterol emboli and renal artery stenosis) are also reported (38,41).…”
Section: Large Seriesmentioning
confidence: 93%
“…97 Interestingly, RTX led to clinical remission in a dialysis-dependent adolescent with GPA who had been dialysis dependent for 22 months despite the use of CYC. 98 Danish investigators randomized 32 patients with GPA to PLEX or no PLEX as part of initial induction therapy (both groups received CYC þ CS). 99 Multivariate analysis demonstrated that PLEX improved renal survival among patients with initial serum creatinine greater than 250 μmol/L (2.85 mg/dL; p < 0.01).…”
Section: Renal Involvementmentioning
confidence: 99%